Post-activation potentiation versus post-activation performance enhancement in humans: Historical perspective, underlying mechanisms, and current issues - Blazevich, A. J.; Babault, N. (Frontiers in Physiology, 2019)
Post-activation potentiation (PAP) is a well-described phenomenon with a short half-life (~28 s) that enhances muscle force production at submaximal levels of calcium saturation (i.e., submaximal levels of muscle activation). It has been largely explained by an increased myosin light chain phosphorylation occurring in type II muscle fibers, and its effects have been quantified in humans by measuring muscle twitch force responses to a bout of muscular activity. However, enhancements in (sometimes maximal) voluntary force production detected several minutes after high-intensity muscle contractions are also observed, which are also most prominent in muscles with a high proportion of type II fibers. This effect has been considered to reflect PAP. Nonetheless, the time course of myosin light chain phosphorylation (underpinning "classic" PAP) rarely matches that of voluntary force enhancement and, unlike PAP, changes in muscle temperature, muscle/cellular water content, and muscle activation may at least partly underpin voluntary force enhancement; this enhancement has thus recently been called post-activation performance enhancement (PAPE) to distinguish it from "classical" PAP. In fact, since PAPE is often undetectable at time points where PAP is maximal (or substantial), some researchers have questioned whether PAP contributes to PAPE under most conditions in vivo in humans. Equally, minimal evidence has been presented that PAP is of significant practical importance in cases where multiple physiological processes have already been upregulated by a preceding, comprehensive, active muscle warm-up. Given that confusion exists with respect to the mechanisms leading to acute enhancement of both electrically evoked (twitch force; PAP) and voluntary (PAPE) muscle function in humans after acute muscle activity, the first purpose of the present narrative review is to recount the history of PAP/PAPE research to locate definitions and determine whether they are the same phenomena. To further investigate the possibility of these phenomena being distinct as well as to better understand their potential functional benefits, possible mechanisms underpinning their effects will be examined in detail. Finally, research design issues will be addressed which might contribute to confusion relating to PAP/PAPE effects, before the contexts in which these phenomena may (or may not) benefit voluntary muscle function are considered.